Bronkoskopi pada Pasien Kritis dengan Atelektasis di ICU - Nurfitriani; Salam, Syamsul H (Jurnal Komplikasi Anestesi, 2023)
Bronchoscopy in critical ill patients in ICU is a procedure may carry higher risk considering that patients are often in unstable hemodynamic and hypoxemia which may increase morbidity rates, so the decision for bronchoscopy must be deeply considered with risks and benefits. We report a female patient admitted to the ICU with loss consciousness and acute respiratory failure. Patients with previous history of myasthenia gravis that reduce her ability to cough. From the physical and radiologic examination, we found signs of lower airway obstruction. The patient underwent bronchoscopy. We found mucus plugs obstructing both the upper and lower lobe of the left bronchus. During the procedure the patient is sedated. Mucus plugs were aspirated and microbiological culture were performed. The patient's condition was stable and clinical improvement was obtained.